Respective Control and Management of Prevalent Diseases and Feeding of Small Ruminants: Training on Optimal Animal Health, Feeding, and Management Practices Throughout Small Ruminants' Reproductive Cycle Kef & Siliana, Tunisia - Tebourbi, Ons; Ben Said, Mohamed Salah; Mannai, Amal; Ouerghi, Emna; Rahali, Khalil; Abdi, Bouthayna; Rekik, Mourad (International Center for Agricultural Research in the Dry Areas, 2024)
Many health and nutritional challenges are confronting small ruminants across the different seasons of their reproductive cycle, starting from mating, pregnancies, and births, to suckling and weaning. As a tentative to overcome these threats, three training sessions were organized under the Agroecology initiative by ICARDA and OEP teams to correct and improve farmers’ existing knowledge on the most prevalent health, feeding, and management issues in small ruminants in different seasons. This document provides a description of these trainings as well as a summary of their main outputs.